(untitled) (International Current Pharmaceutical Journal, 2012)
Retrospective DUE is the reviewing of drug therapy after the patient has received the medication. Asthma is a common chronic disease in Malaysia. A National Health and Morbidity Survey in 1996 indicated that asthma prevalence in Malaysia was 4.2%. Statistics on the causes of death have noted asthma as one of the 10 principal causes of death (7.3%) in Malaysia. The purpose of the study was to compare drug utilization patterns amongst the asthmatics from the past two years (since 2009) in Kedah state. Asthmatics admitted to the hospital in the preceding two years were analyzed by their patient charts. This study focused on both smoker and non smoker asthmatics. It was observed that salbutamol was most commonly prescribed, followed by montelukast and prednisolone. In the combination therapy, the most commonly prescribed was Symbicort, followed by seretide and combivent. Corticosteroids constituted the most prevalent class, followed by beta-2 agonists, leukotriene modifiers and methylxanthines. The study presented the most recent scenario on drug utilization pattern of asthmatics in Kedah state. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12060 International Current Pharmaceutical Journal 2012, 1(11): 353-360